Analysis of the Study on the Application of GSTC Criteria as an Instrument of Cultural Sustainability at the Kacirebonan Palace - Ari Wibowo, Toni; Puarag, Peri (Ann Publisher, 2024)
Research has been conducted to analyze the application of GSTS criteria as an instrument for crocodile sustainability in the Kacirebonan palace. The method used in this study is a descriptive method with surveys, interviews, and literature studies from sharing related sources and documentation. The study results show that the Kacirebonan Palace has the potential for tourist objects and attractions that can be used as a tourism destination in developing the Kacirebonan Palace. Cultural tourist attractions are an advantage owned by the Kacirebonan Palace. Introducing culture to tourists who visit will positively impact the culture so that the culture is maintained and sustainable. The research uses two stages, the first stage identifying the types of tangible and intangible culture in the Kacirebonan Palace. The second stage is to interpret and analyze the results of data collection activities that are described qualitatively in a systematic and structured manner based on applying the GSTC criteria as an instrument of cultural sustainability in the Kacirebonan Palace. The Kacirebonan Palace, as one of the tourist destinations that is still developing, still needs various improvements and improvements in cultural sustainability based on the GSTC criteria as an instrument of cultural sustainability in the Kacirebonan Palace.